Peran Strategis Informatika Manajemen dalam Mendorong Transformasi Digital: Sebuah Tinjauan Sistematis Literatur - Tribuana, Dhimas; Puspita Ayu, Novalinda; Said Uddin, Abu; Firdania, Andi; Dewi Haryanti Agustan , Andi; Rusli, Muhammad (Jurnal Teknologi dan Bisnis Cerdas, 2025)
Digital transformation (DT) has become one of the most critical strategic issues in modern organizational management across both public and private sectors. This study adopts a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework to examine 45 scholarly articles published between 2006 and 2025. The analysis aims to identify overarching patterns, key contributions, research gaps, and future research directions in the context of DT. The synthesis reveals five main clusters: (1) Governance & Alignment as the digital governance foundation ensuring strategic coherence, (2) Digital Capabilities & Dynamic Capabilities as performance and innovation enablers, (3) Artificial Intelligence & Generative AI as drivers of innovation as well as ethical challenges, (4) Public Sector & Smart Governance focusing on public values, transparency, and policy legitimacy, and (5) SMEs & Sustainability emphasizing contextual adaptation, resource constraints, and long-term resilience. The resulting conceptual model highlights that DT success is not solely determined by technology adoption, but by the interaction between governance, capabilities, value orientation, and socio-economic context. This study contributes to the literature by providing an integrative cross-cluster framework and offering implications for management practice and public policy. The findings are expected to serve as a reference for scholars, practitioners, and policymakers in developing inclusive, adaptive, and sustainable DT strategies.